Enterprise Information Systems 10th International Conference, ICEIS 2008, Barcelona, Spain, June 12-16, 2008, Revised Selected Papers - Filipe, Joaquim; Cordeiro, José (Lecture Notes in Business Information Processing, 2009)
This books contains the best papers of the 10th International Conference on Enterprise Information Systems, ICEIS 2008, held in Barcelona, Spain, in June 2008. Two invited papers are presented together with 24 papers which were carefully reviewed and selected from 62 full papers accepted for presentation at the conference itself (out of 665 submissions). The topics covered are: databases and information systems integration; artificial intelligence and decision support systems; information systems analysis and specification; software agents and internet computing; and human-computer interaction.